2014
DOI: 10.1517/17460441.2014.908180
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing treatments for nicotine dependence by increasing cognitive performance during withdrawal

Abstract: Introduction Current FDA-approved smoking cessation pharmacotherapies have limited efficacy and are associated with high rates of relapse. Therefore, there is a clear need to develop novel antismoking medications. Nicotine withdrawal is associated with cognitive impairments that predict smoking relapse. It has been proposed that these cognitive deficits are a hallmark of nicotine withdrawal that could be targeted in order to prevent smoking relapse. Thus, pharmacotherapies that increase cognitive performance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 140 publications
(171 reference statements)
1
33
0
Order By: Relevance
“…Smokers who were better able to focus during the imagery waited longer before smoking a cigarette. Greater proficiency in the mental simulation will likely require fewer cognitive resources when smoking abstinence-induced cognitive deficits are common (Ashare & Schmidt, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smokers who were better able to focus during the imagery waited longer before smoking a cigarette. Greater proficiency in the mental simulation will likely require fewer cognitive resources when smoking abstinence-induced cognitive deficits are common (Ashare & Schmidt, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that smoking latency was longer the better participants were able to imagine smoking a cigarette. The ability to focus on the imagery in the context of abstinence-associated cognitive deficits may be mitigated by nicotine replacement or pro-cognitive medications (Ashare & Schmidt, 2014). Finally, the exclusion of individuals with a psychiatric disorder was based on self-report and the use of psychotropic medication, not on clinical interview.…”
Section: Discussionmentioning
confidence: 99%
“…Given that cognitive deficits during nicotine withdrawal predict smoking relapse [115, 116], these results suggest that AChEIs may improve cognitive performance in abstinent smokers and prevent smoking relapse. Taken together, these studies suggest that AChEIs could be re-purposed as pharmacotherapies for smoking cessation [117]. …”
Section: Neurotransmitter Mechanisms Regulating Nicotine Seekingmentioning
confidence: 99%
“…These include mild-to-moderate impairment in a number of frontally mediated cognitive functions including sustained attention, working memory and response inhibition (al-Adawi & Powell, 1997; Ashare, Falcone, & Lerman, 2014; Dawkins, Powell, West, Powell, & Pickering, 2007; Powell, Dawkins, & Davis, 2002; Wesnes, Edgar, Kezic, Salih, & de Boer, 2013). The reversal of these withdrawal-associated cognitive deficits has been proposed as a potential target for medication development efforts aimed at increasing smoking cessation rates (Ashare et al, 2016; Ashare & Schmidt, 2014). …”
Section: Introductionmentioning
confidence: 99%